Correlation analysis of the HLA‐DPB105:01 and BTNL2 genes within the histocompatibility complex region with a clinical phenotype of psoriasis vulgaris in the Chinese Han population - Guo, Huimin; Huang, Yong; Wu, Juan; Zheng, Xiaodong; Ye, Lei; Huang, Hequn; Wang, Wenjun; Zhen, Qi; Wu, Jing; Qian, Wenjun; Cheng, Hui; Fan, Xing; et al. (The journal of gene medicine, 2017)
Background The human major histocompatibility complex (MHC) is known to be highly polymorphic and has been identified to be associated with numerous diseases. The HLA‐DPB1 and BTNL2 genes were associated with psoriasis for the first time. The present study aims to investigate the relevance of the HLA‐DPB1 and BTNL2 genes with respect to clinical phenotypes of psoriasis vulgaris (PV). Methods To investigate whether the HLA‐DPB1 and BTNL2 polymorphisms were associated with clinical phenotypes of PV in Chinese Han population, we conducted an analysis in case–controls and case‐only subjects (9906 controls and 8744 cases) via MHC targeted sequencing stratified analysis. Results In cases and controls, analysis showed that the genotype of HLA‐DPB1*05:01 was associated with type of guttate [p = 3.914 × 10−2, odds ratio (OR = 0.9335)] and northern region (p = 1.182 × 10−3, OR = 0.9108). In the case‐only analysis, the genotype of HLA‐DPB1*05:01 was significantly correlated with geographical region (p = 1.36 × 10−3, OR = 1.134). In cases and controls, analysis showed that the genotype of BTNL2 (rs 41355746) was associated with being male (p = 2.563 × 10−2, OR = 0.8897), early‐onset (p = 9.399 × 10−3, OR = 0.8856), guttate (p = 2.469 × 10−2, OR = 0.8558) and family history (p = 1.51 × 10−4, OR = 0.772). In the case‐only analysis, the genotype of BTNL2 (rs41355746) was significantly correlated with family history (p = 1.768 × 10−3, OR = 0.757) and age of onset (p = 3.818 × 10−2, OR = 1.195). Conclusions The results of the present study indicate that the HLA‐DPB1*05:01 gene was associated with the geographical region of PV and the BTNL2 gene was significantly associated with family history and age of onset of PV. In conclusion, the HLA‐DPB1*05:01 and BTNL2 genes might be responsible for the complicacy of clinical features.